2021
DOI: 10.3390/molecules26061611
|View full text |Cite
|
Sign up to set email alerts
|

7-(2-Anilinopyrimidin-4-yl)-1-benzazepin-2-ones Designed by a “Cut and Glue” Strategy Are Dual Aurora A/VEGF-R Kinase Inhibitors

Abstract: Although overexpression and hyperactivity of protein kinases are causative for a wide range of human cancers, protein kinase inhibitors currently approved as cancer drugs address only a limited number of these enzymes. To identify new chemotypes addressing alternative protein kinases, the basic structure of a known PLK1/VEGF-R2 inhibitor class was formally dissected and reassembled. The resulting 7-(2-anilinopyrimidin-4-yl)-1-benzazepin-2-ones were synthesized and proved to be dual inhibitors of Aurora A kinas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…The synthesis of N-substituted benzazepinones belonging to series II is displayed in Fig 13 . Alkylation of the starting material 11 [ 51 ] with tert -butyl bromoacetate led to ester 12 , which subsequently was deprotected using phosphoric acid in toluene according to a procedure reported by Li et al . [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The synthesis of N-substituted benzazepinones belonging to series II is displayed in Fig 13 . Alkylation of the starting material 11 [ 51 ] with tert -butyl bromoacetate led to ester 12 , which subsequently was deprotected using phosphoric acid in toluene according to a procedure reported by Li et al . [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of the following compounds was prepared according to published procedures: 8-chloro-3,4-dihydro-1 H -benzo[ b ]azepin-2,5-dione ( 6 ) [ 50 , 80 ], 4-iodophenylhydrazine [ 81 ], 1,3,4,5-tetrahydro-2 H -benzo[ b ]azepin-2-one ( 11 ) [ 51 ], 3,3-dimethyl-1,3,4,5-tetrahydro-2 H -benzo[ b ]azepin-2-one ( 14 ) [ 53 , 82 ], 5,7-dihydro-6 H -dibenzo[ b , d ]azepin-6-one ( 17 ) [ 55 , 56 ] and ( E )-5-methoxyimino-1,3,4,5-tetrahydro-2 H -benzo[ b ]azepin-2-one ( 20 ) [ 58 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the aforementioned compounds exhibited the potential to be developed into other dual-target inhibitors. For example, studies recently reported the synthesis of potent dual-target Aurora A/VEGF-R inhibitors generated by the reassembly of the pyrimido­[5,4- d ]­[1]­benzazepin-6-one scaffold …”
Section: Recent Progress In Plk1i Development For Cancer Therapymentioning
confidence: 99%